PENGARUH KEDEKATAN EMOSIONAL DAN KOMUNIKASI PEMASARAN TERHADAP LOYALITAS KONSUMEN MINIMARKET NAMORA KOTA BENGKULU - Melda Yunita; Lia Kontesa (UM. Bengkulu, 2022)
This study aims 1). The effect of emotional closeness on consumer loyalty of Namora minimarket Bengkulu City, 2). The effect of marketing communication on consumer loyalty of Namora Bengkulu City minimarkets, 3). The influence of emotional closeness and marketing communication on consumer loyalty of Namora Bengkulu City minimarket. This study used a descriptive quantitative reseach method. The population of this study were all of customers of Namora minimarket in Bengkulu City. The sampel was 100 customers that taken by using accidental sampling tecnique. The data was processed by using the Classical Assumption Test Technique, Multiple Linear Regression Analysis Technique, Coefficient of Determination Analysis (R2), and Partial Test (t-test), Simultaneous Test (f-test). The results of this study indicate that partially the emotional closeness variable has a significant effect on the consumer’ loyalty variable, H1 is accepted and marketing communication has a significant effect on the consumer loyalty variable, H2 is accepted. Meanwhile, the f test of emotional closeness (X1) and marketing communication (X2) has a significant influence on consumer’ loyalty (Y) of Namora Minimarket in Bengkulu City, so that H3 is accepted. The overall significant level is (sig = 0.000 < 0.05) with a regression equation Y = 0.650 + 0.734 (X1) + 0.345 (X2), and the coefficient of determination (R2) R Square value is 0.761. The coefficient of determination means that together emotional closeness and marketing communication make a big contribution in consumer’ loyalty of Namora Minimarket in Bengkulu City. The most dominant factor with the largest regression coefficient value is the emotional closeness variable (X1) with a value of 0.734. Keywords : Emotional Closeness, Marketing Communication, Consumer Loyalty